Crystal Structure Determination of Mebendazole Form A Using High-Resolution Synchrotron X-Ray Powder Diffraction Data - Ferreira, Fabio Furlan; Antoni, Selma Gutierrez [UNESP]; Pires Rosa, Paulo Cesar; Paiva-Santos, Carlos de Oliveira [UNESP] (John Wiley & Sons Inc, 2010)
The crystal structure determination of mebendazole form A, an anthelmintic drug, was performed for the first time by applying the DASH software program to synchrotron X-ray powder diffraction data, and supported by a satisfying Rietveld fit. This polymorph of mebendazole crystallizes in a triclinic (P (1) over bar) space group, with unit-cell parameters a = 5.5044(2)angstrom, b = 11.2872(2)angstrom, c = 12.5276(5)angstrom, a= 66.694(2)degrees, beta = 82.959(2)degrees, gamma = 78.443(2)degrees, V = 699.52(5)angstrom(3), Z = 2, M = 295.293 g mol(-1), rho(calc) = 1.4021 g cm(-3), and rho(meas) = 1.3935(66) g cm(-3), which were obtained by means of the unit-cell formula weight and a picnometric measurement, respectively. The goodness-of-fit and R-factors were, respectively: chi(2) = 1.746, R(F)(2) = 1.69%, R(wp) = 5.72%, and R(p) = 4.37%. A weak nonclassical hydrogen bond involving the atoms N(3)-H(23)center dot center dot center dot O(11) may be responsible for the greater stability of the polymorphic form A of mebendazole due to the strongest electronegativity of nitrogen. (C) 2009 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 99:1734-1744, 2010
Keywords: X-ray powder diffractometry; crystal structure; polymorphism; crystallography; ab initio calculations; quantitative phase analysis; synchrotron; mebendazole; polymorph A; anthelmintic drug